Molecular cloning and expression of a modified Tn5 transposase for the enhancement of in Vitro transposition in bacteria and yeast - Ng, Wen Guang (2019)
Transposable elements are DNA elements that translocate and integrate into other DNA locations through transposition mediated by the enzyme transposase (Tnp). The Tn5 transposon, which is one of the most well-studied bacterial DNA transposons, encodes its own Tnp. Previous studies showed modifications in the Tnp amino acid sequence increased the Tn5 Tnp activity, producing higher transposition frequency. In-house production of transposases is known to be tedious, due to its cytotoxicity. Although Tnp is widely used in prokaryotic DNA transposition, successful application of transposase-mediated DNA transposition is lacking and the efficiency reported was very low, especially in eukaryotes. Nuclear localisation signals (NLSs) are peptide motifs that facilitate nuclear import. Therefore, fusing NLS to Tnp may improve transposition efficacy in eukaryotes. In this study, wild type Tnp, hyperactive Tnp (Tnp*) and NLS-Tnp* genes were constructed and cloned into expression vectors pLATE11. Next, a protocol for expressing and purifying functionally active Tnp with hyperactivity was developed. Furthermore, the efficiency of transposition mediated by the hyperactive Tnp* with and without an NLS fusion was tested in E. coli and yeast. The concentration of the selective antibiotics carbenicilin and the inducer IPTG were tested for obtaining the suitable conditions to improve the protein expression and purification. The purified proteins were used for in vitro DNA transposition experiments in E. coli and yeast. Interestingly, the NLS fusion to that Tnp* protein aided in the purification of the recombinant Tnp protein, and increased the transposition frequency in vitro in E. coli. However, NLS-Tnp*-mediated transposition was not detected in yeast. This might be due to the poor nuclear import efficiency conferred by a single NLS. Therefore, in future studies, multiple copies of NLS may be tested for increasing the transposition efficacy in yeast. Besides, further yeast electroporation protocol needs to be optimised for improving yeast transformation.